The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1415-790x201400010020eng
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of pulmonary tuberculosis in Mato Grosso do Sul, Brazil

Abstract: This study sought to show the importance of discussing territoriality more adequately in Brazil. A continuous reevaluation of all health programs is needed for populations in each of the areas where they live. Then, it will be possible to correct the incidence rate of tuberculosis for specific populations in the state, taking into account populations in each place of residence and considering their specificities and differences. In conclusion, in the light of the present study, it is necessary to discuss more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
8
0
4
Order By: Relevance
“…These data show a higher incidence in such population, according to studies which concluded that indigenous groups are the most vulnerable to TB infection. [22][23][24][25] Regarding the georeferenced analysis of TB cases in nonindigenous populations, few cities showed a decrease in the mean coefficient of incidence during the transition from the 2005-2007 to the 2008-2010 three-year period. Nonetheless, there was a steady reduction in the incidence of cases in the group of cities included in the 6 th and 10 th CRS.…”
Section: Discussionmentioning
confidence: 99%
“…These data show a higher incidence in such population, according to studies which concluded that indigenous groups are the most vulnerable to TB infection. [22][23][24][25] Regarding the georeferenced analysis of TB cases in nonindigenous populations, few cities showed a decrease in the mean coefficient of incidence during the transition from the 2005-2007 to the 2008-2010 three-year period. Nonetheless, there was a steady reduction in the incidence of cases in the group of cities included in the 6 th and 10 th CRS.…”
Section: Discussionmentioning
confidence: 99%
“…13 The increase in the rate of abandonment of treatment, the deterioration of health services due to the decrease of investments in the sector are also problems faced in the Rio de Janeiro city. 37,38 In Brazil, the scarcity of recent studies on the epidemiology of MDR-TB in the country makes difficult the process of showing the real situation the disease in territory based on its determining and conditioning factors, be they social, cultural or clinical-epidemiological.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação à etnia, na maioria das notificações os pacientes se intitularam brancos, em concordância com outros estudos. Essa informação pode estar associada ao modo como as pessoas se definem no ato do preenchimento da notificação, e não a uma predominância real da doença por raças 19,21 . A situação de rua e a institucionalização podem ser considerados ambientes de grande vulnerabilidade devido à aglomeração de pessoas, pouca condição de higiene, nutrição precária, uso de álcool e drogas, e difícil acesso aos serviços de saúde.…”
Section: Discussionunclassified